Studi Kualitatif Persepsi Pengurus Gereja Terhadap Pelaporan Keuangan Berbasis Isak 35 - Yusni Warastuti; Clara Susilawati; Sansaloni Butar-Butar; Monika Palupi Murniati (JEMAP, 2022)
The church as a non-profit oriented entity accepts donations to fund its service activities and donors do not expect a comparable return of economic benefits. Legitimacy theory can be used to explain the position of the church which has a social contract with the people so that it is still necessary to make accountability. Interpretation of Financial Accounting Standards 35 as a substitute for Statement of Financial Accounting Standards No. 45 is a guideline for non-profit oriented entities to present financial statements, including churches. This study aims to explore the understanding of church managers on the components of financial statements and their usefulness. This study is a qualitative research with a phenomenological approach with five church administrators informants on the implementation of ISAK 35 as of January 1, 2020. The method used in this study used interviews with in-depth interviews. The analysis technique in the study after conducting the interview was transcription, description and interpretation of the data obtained. The results showed that the guidelines used to prepare the financial statements of PSAK 45. Other results, the informants already had a basic understanding, namely being able to mention the main accounts in each financial report and provide an explanation of their use, except for the cash flow statement because this report is not a component of financial statements that served. The existing financial reports are sufficient to be used as a basis for church management, starting from planning, controlling and making decisions.